STRENGTHENING THE IMPLEMENTATION OF THE INDEPENDENT CURRICULUM, ESPECIALLY IN PANCASILA STUDENT PROFILE STRENGTHENING PROJECT (P5) FOR SD/MI TEACHERS - Sumantri, Mohamad Syarif; Khasanah, Uswatun; Sutisnawati, Astri; Sinyanyuri, Sonya (Jurnal Graha Pengabdian, 2025)
The Ministry of Education, Culture, Research, Technology and Technology (Kemenristekdikti) of Indonesia has launched a new policy in education with the issuance of an independent curriculum. The Pancasila Student Profile Strengthening Project (P5) is one of the main focuses of the independent curriculum with the aim of shaping student character and competencies based on Pancasila values. Teachers need preparation and a deep understanding of concepts in implementing the independent curriculum, especially the project to strengthen the profile of Pancasila students at the elementary school level. However, the facts in the field reveal that there are still many elementary / middle school teachers who do not fully understand the concepts and learning methods that are in accordance with this new curriculum. This can hinder the effectiveness of curriculum implementation in the field. This training and community service activity aims to improve the understanding and competence of elementary school teachers in implementing the Independent Curriculum, with a special focus on the Pancasila Student Profile Strengthening Project (P5) in learning. The implementation method of this training activity is directly face-to-face in the classroom. Guided training is a method in community service activities. An active and participatory approach is also used in this training activity with presentation and discussion activities, case studies, learning simulations, P5 project design practices, reflection and feedback. The results of community service activities carried out by the team were considered successful in improving the understanding and ability of teachers in implementing the Pancasila Student Profile Strengthening Project (P5), this is proven in the evaluation data of the pretest and pot-test there was an increase as much as... This service and training activity provides effective evidence in improving teachers' understanding and ability in implementing the Pancasila Student Profile Strengthening Project (P5).